Pengembangan Model Pembelajaran Bahasa Arab Berbasis Teori Multiple Intelligence - Zainal Arifin Ahmad (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2015)
The discovery of the theory of Multiple Intelligence by Howard Gagner has changed the paradigm of education and learning. If the old paradigm view that intelligence is a single learner who is only measured by IQ tests, then the paradigm of Multiple Intelligence view that intelligence is plural learners. Each individual has the advantage of certain intelligence that may be different with advantages that others have. That fact has implications for the importance of changing patterns of education and learning, including learning Arabic, from the pattern that is only oriented to the development of intellectual intelligence (IQ) to the pattern of intelligence that takes into account the diversity of learners. This paper describes showing the development of Arabic language instruction model based on the theory of Multiple Intelligence. The model in question is a model of the development of Arabic language learning component which includes the development of Arabic language learning goals, teachers’ roles, attitudes and treatment of students, and the development of materials, methods, media, and evaluating the results of learning Arabic, all of which were based on intelligence insight plural (Multiple Intelligence).